Comparing smoke emissions and impacts under alternative forest management regimes - Jonathan W. Long; Stacy A. Drury; Samuel G. Evans; Charles J. Maxwell; Robert M. Scheller (Ecology and Society, 2022)
Smoke from wildfires has become a growing public health issue around the world but especially in western North America and California. At the same time, managers and scientists recommend thinning and intentional use of wildland fires to restore forest health and reduce smoke from poorly controlled wildfires. Because of the changing climate and management paradigms, the evaluation of smoke impacts needs to shift evaluations from the scale of individual fire events to long-term fire regimes and regional impacts under different management strategies. To confront this challenge, we integrated three widely used modeling tools to analyze smoke impacts across different management scenarios within a future of changing climate. We applied this multi-stage framework to a case study analysis in the Lake Tahoe basin, in which managers proposed scenarios that involved varying levels of hand- and mechanical-thinning treatments and prescribed fires. We began by using the LANDIS-II model to project daily emissions of fine particulate matter from wildland fires under various climate and management scenarios over a century. We also modeled dispersion and health impacts based upon individual wildfire events selected to be representative of different management scenarios. For those events, we modeled smoke conveyance to downwind communities from representative future fires using the BlueSky smoke dispersion model. Lastly, we estimated human health impacts resulting from the modeled smoke using the U.S. Environmental Protection Agency's BenMAP model. Our results suggest that emissions from wildfires will substantially increase in future decades; however, increased levels of forest thinning could substantially reduce those emissions and harmful health impacts from large wildfires. We also found that increased use of prescribed burning could reduce the health impacts associated with large wildfires but would also increase the frequency of low levels of emissions. Furthermore, the modeling results suggested that individual prescribed fires could have substantial health impacts if dispersion conditions are unfavorable. Our results suggest that increased management is likely to yield important benefits given expected increases in wildfire activity associated with climate change. However, there remain many challenges to projecting the effects of alternative management regimes, especially ones that involve substantial increases in intentional burning.